Psychoanalytic quarterly. (New York Psychoanalytical Quarterly Press)
"Primitive high gods, by Gʹeza Rʹoheim": v. 3, no. 1, pt. 2 (133 p.).
Editors: Apr. 1932-<Oct. 1934> D. Feigenbaum, B.D. Lewin, G. Zilboorg (with F.E. Williams, Apr. 1932-July 1934).
Vols. 1-35, 1932-66. 1 v. ; vols. 46-55, 1977-86. 1 v.
Keywords: Psychoanalysis -- Periodicals